Analisis Kelayakan Kegrafikan dalam Buku Teks Cerdas Berbahasa Indonesia untuk SMA/MA Kelas XII Kurikulum 2013 Revisi Terbitan Erlangga - Jeny Marsela; Julianita; Mifta Kusriyah; Muhammad Danil; Muhammad Gadink; Muhammad Mukhlis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This study aims to determine the graphical analysis of the Indonesian class XII textbooks. The object of this research is the Indonesian Language Smart Textbook for SMA/MA Class XII 2013 Revised Curriculum published by Erlangga. This book is suitable for use based on the assessment of the data studied from several subcomponents, namely, point of view, clarity of concepts, relevant to the curriculum, attracting interest, fostering motivation, stimulating student activity, illustrative, easy to understand, supporting other subjects, appreciating individual differences and establish values. All sub-components produced good assessment results on the Indonesian Language Smart Textbook for SMA/MA Class XII 2013 Revised Curriculum published by Erlangga. Thus, this textbook is suitable for use by teachers and students to achieve learning objectives. The existence of a broad scope regarding the feasibility of textbook graphics is certainly one of the inspirations for further researchers to study further and more deeply. Hopefully this research can be a reference for further research on the feasibility analysis of textbooks and assist teachers in choosing appropriate textbooks for use in classroom learning.